Upaya Meningkatkan Prestasi Belajar Mata Pelajaran Pendidikan Agama Islam Materi Zakat dengan Penerapan Metode Tanya Jawab pada Siswa Kelas X TL-2 SMK Negeri 2 Karang Baru Kabupaten Aceh Tamiang - Sri Rahayu (Pedagogika: Jurnal Ilmu-Ilmu Kependidikan, 2022)
The purpose of this research is: To improve the Learning Achievement of Islamic Religious Education Subject on Zakat Material in Class X TL-2 Students of SMK Negeri 2 Karang Baru, Aceh Tamiang District Through the Application of the Question and Answer Method. This study used two rounds of action research. Each round consists of four stages: design, activity, observation, and reflection. The target of this study were students of Class X TL-2 SMK Negeri 2 Karang Baru Aceh Tamiang District. The data obtained is in the form of formative test results, observation sheets of teaching and learning activities. From the results of the analysis it was found that student learning achievement increased from cycle I first meeting to cycle II second meeting namely, cycle I first meeting 50%, cycle I second meeting 68%, and cycle II first meeting 77%, cycle II second meeting 86% , classically students achieve mastery of learning outcomes. The conclusion of this study is: Through the application of the Question and Answer Method, it can improve learning achievement in Islamic Education Subject Zakat Materials in Class X TL-2 Students of SMK Negeri 2 Karang Baru Aceh Tamiang Regency which is marked by an increase in student learning completeness, that is, in the first cycle the first meeting of students who completed only 50%, the second meeting in the first cycle increased to 68%, and in the second cycle the first meeting the students completed 77%, in the second cycle the second meeting 86% (completed classical).